Rola systemu zarządzania wiedzą w doskonaleniu jakości procesów i produktów w przedsiębiorstwie - Kobyłko, Grzegorz; Tabaszewska, Edyta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of the paper is to present the role of knowledge management system in processes and products quality improvement in an enterprise. In authors' opinion, the knowledge management in both cases can make this process more effective- by integrating different attitudes to management or by supervising the knowledge about the customer's needs. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 177-185